2001
DOI: 10.4049/jimmunol.167.3.1482
|View full text |Cite
|
Sign up to set email alerts
|

Human IFN-α Protein Engineering: The Amino Acid Residues at Positions 86 and 90 Are Important for Antiproliferative Activity

Abstract: Human IFN-α is a family of structurally related proteins that exhibit a wide range of antiproliferative activities. To understand the structural basis for these different antiproliferative activities, eight recombinant human IFN-α hybrids (HY) of α21a/α2c (HY-4, HY-5) and mutants (site-directed mutagenesis (SDM)-1, 2 and cassette mutagenesis (CM)-1, 2, 3, and 4) have been expressed, purified, and characterized. The data showed that the amino acid region 81–95 is important for antiproliferative activity. Site-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…This could explain the tenfold lower antiproliferative activity of CM3 than that of IFN-α2c in 48 hours antiproliferative assay. It did however not explain the 800-fold lower ability of CM3 (with 6-histidine tag) to compete with IFN-α2c (with 6-histidine tag) for receptor binding site (17).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…This could explain the tenfold lower antiproliferative activity of CM3 than that of IFN-α2c in 48 hours antiproliferative assay. It did however not explain the 800-fold lower ability of CM3 (with 6-histidine tag) to compete with IFN-α2c (with 6-histidine tag) for receptor binding site (17).…”
Section: Discussionmentioning
confidence: 94%
“…Our previous results showed that hybrid IFNs with N-terminal portion derived from IFN-α21b competed poorly with IFN-α2b for cellular binding (12,17). CM3 is one of these hybrids, and also has a mutation in helix C (Y86K).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations